Trading and Shareholder Democracy - Doron Levit; Nadya Malenko; Ernst Maug (The Journal of Finance, 2023)
We study shareholder voting in a model in which trading affects the composition of the shareholder base. Trading and voting are complementary, which gives rise to self-fulfilling expectations about proposal acceptance and multiple equilibria. Prices and shareholder welfare can move in opposite directions, so the former may be an invalid proxy for the latter. Relaxing trading frictions can reduce welfare because it allows extreme shareholders to gain more weight in voting. Delegating decision-making to the board can help overcome collective action problems at the voting stage. We also analyze the role of index investors and social concerns of shareholders.
Keywords: 330